Comparison of weight-adjusted dose versus fixed dose ondansetron in preventing shivering following spinal anaesthesia for caesarean deliveries - Gicheru, Moses (Afr Health Sci, 2019)
BACKGROUND: Spinal anaesthesia is an effective regional anaesthesia technique, which is preferred in almost 86% of caesarean sections in the United States and United Kingdom. Eighty percent of caesarean sections done at the Aga Khan University hospital are under spinal anaesthesia. Shivering is a common complication of spinal anaesthesia, it occurs in 40%-64% of patients after neuraxial anaesthesia. Shivering may cause maternal and fetal hypoxemia, maternal discomfort and a problem to the anaesthesiologists when it comes to monitoring the patient during caesarean sections. Ondansetron a 5-HT3 receptor antagonist is effective in treatment and prevention of post-spinal anesthesia shivering. In published studies, use of a fixed dose in patients with different weights, masked the dose effect ondansetron in preventing shivering, such that not adjusting the dose according to the weight of patients' resulted in a higher occurrence of shivering. No study has compared different doses of ondansetron in preventing shivering in parturient women who have had spinal anaesthesia for caesarean section. OBJECTIVES: To determine if a weight-adjusted dose is better than a fixed dose of ondansetron in preventing shivering following spinal anesthesia for caesarean delivery. METHOD: This was a randomized, double-blinded controlled trial of 124 women scheduled for elective caesarean surgery. The women were randomized into two equal groups. The intervention group received intravenous ondansetron weight adjusted dosing at 0.1mg/kg and the control group received a fixed dose of 4mg before spinal anesthesia. The occurrence and severity of shivering and other outcomes, such as headache, pruritus were assessed and recorded during the surgery and post-operative period. RESULTS: A total of 124 patients were included in the study. Social demographic data and baseline vital signs did not differ significantly between the groups. Shivering was observed in 14 patients (22.6%) in the control group that received 4mg ondansetron and 7 patients (11.3%) in the intervention group that had 0.1mg/kg of ondansetron, but there was no statistical difference between the groups (p- value 0.090). The severity of shivering was greater in the control group compared to intervention group where patients who developed grade two shivering were 8.1% to 0% respectively. (P value 0.047). There was no difference in the occurrence of pruritus between the two groups. No patient required treatment for very severe shivering. CONCLUSION: This study, found that ondansetron weight adjusted dose at 0.1mg/kg, reduced the severity of shivering when compared to a fixed dose ondansetron at 4mg.